EVALUASI KINERJA ISOLASI DAN PARAMETER LISTRIK PADA CAPACITIVE VOLTAGE TRANSFORMER (CVT) DI BAY TANJUNG 2 GARDU INDUK 150 KV SWITCHING - Ramadhan, Anur; Muljono, Agung Budi (Jurnal Informatika dan Teknik Elektro Terapan, 2025)
One of the important components in a substation is the Capacitive Voltage Transformer (CVT). Maintenance is one of the activities aimed at keeping equipment in optimal condition to ensure it performs its functions reliably. One type of maintenance is shutdown measurement. This study examines insulation resistance, tan delta, and capacitance of the CVT equipment at Bay Tanjung 2 of the 150 kV Switching Substation. The insulation resistance test refers to the Decree of the Board of Directors of PT.PLN (Persero) No. 0520-2.K/DIR/2014 Transformer Maintenance Manual, which is based on the VDE standard. The tan delta and capacitance tests refer to the IEC 60044-5 standard “Instrument Transformers Part-5,” First Edition, 2004.The results of the CVT insulation resistance tests for phase R were 1.96 GΩ, 2.06 GΩ, 2.24 GΩ, 323 MΩ, 450 MΩ, and 948 MΩ. For phase S, the results were 14 GΩ, 16.71 GΩ, 19.56 GΩ, 496 MΩ, 252 MΩ, and 826 MΩ. For phase T, the results were 19.48 GΩ, 17.2 GΩ, 8.76 GΩ, 1.13 GΩ, 2.46 GΩ, and 2.5 GΩ. The tan delta test results for phases R, S, and T were 0.683%, 0.69%, and 0.701%. The capacitance test results for phases R, S, and T were 4446 pF, 4439 pF, and 4447 pF, respectively.